Tertiary lymphoid structures in colorectal cancer liver metastases: association with immunological and clinical parameters and chemotherapy response - Ahmed, Azaz; Halama, Niels (Anticancer research, 2020)
Background/Aim: The presence of TLS (tertiary lymphoid structures) is detectable in the microenvironment of human cancers and linked to better patient outcomes. The role of TLS in colorectal cancer liver metastases (CRCLM) is unclear. Patients and Methods: Medical records of patients with CRCLM were reviewed (n=33) and corresponding tissue samples (n=21) were obtained. Whole slide imaging analyses on immunohistochemical staining of immune cell infiltrates and TLS were correlated to clinical outcomes (including chemotherapy response) and other parameters. Results: Neither the size (p=0.6) nor the quantity (p=0.47) of TLS was associated with the clinical course. When considering spatial differences, TLS in the invasive margin (IM) were associated with progression-free survival (p=0.03), while TLS in the LM (liver metastasis) were not. Also, TLS in the IM were associated with the presence of CD3+ T cells, which itself was prognostically favorable (p<0.001). Conclusion: TLS in the IM are associated with good prognosis in CRCLM, but not chemotherapy response.
Gesehen am 04.01.2021